2018
DOI: 10.5147/ajb.v0i0.179
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Pomological Variability Analysis of Walnut (Juglans regia L.) Genetic Resources from the Middle and High Atlas of Morocco

Abstract: The walnut (Juglans regia L.) is a traditional fruit crop in Morocco. This species is cultivated in mountain in different environments. However, little data is available on its genetic diversity and its adaptability. Morphological characters of leaf and fruit from 11 Moroccan accessions of walnut were used to assess phenotypic variation of this species. Significant differences were found between accessions for the most examined traits, indicating a high phenotypic diversity. Multivariate analyses lead to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…This study revealed that analysis of biochemical parameters showed significant differences between Moroccan walnut accessions. These results are strengthening by previous work on the same accessions by using morphological and pomological traits (Kabiri, Bouda, Elhansali, & Haddioui, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study revealed that analysis of biochemical parameters showed significant differences between Moroccan walnut accessions. These results are strengthening by previous work on the same accessions by using morphological and pomological traits (Kabiri, Bouda, Elhansali, & Haddioui, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…According to hierarchical analysis based on biochemical parameters, the Moroccan walnut accessions were structured into four distinct groups independently of the mountain range type. Corroborating it, the results obtained by Kabiri et al (2018) by analyzing the same accessions using pomological and morphological traits. The first group included Aghbala accession, seems to diverge significantly from the others, has the highest level of flavonoids, Zn and B.…”
Section: Discussionmentioning
confidence: 96%
“…More strength shells can better protect the kernels against the harmful organisms that feed on prevent the penetration of fungal pathogens (Korac et al., 1998). Shell thickness ranged from 0.73 to 2.95 mm and is similar to the ranges observed for this character in walnut from different countries (Akca et al., 2015; Kabiri et al., 2018; Karadag & Akca, 2011; Sharma et al., 2014). Generally, the most desirable shell thickness in walnut is 0.70–1.50 mm (Zhadan & Strukov, 1977).…”
Section: Resultssupporting
confidence: 79%
“…Nut weighted from 5.53 to 19.24 g with an average of 10.67 (Table 1). The range of 6.00–16.89 g has been reported for nut weight in walnut from different countries (Ahandani et al., 2014; Cosmulescu, 2013; Ghasemi et al., 2012; Kabiri et al., 2018; Karadag & Akca, 2011). Akça et al.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation